Meningkatkan Kemampuan Bicara dan Menulis pada Lansia Demensia dengan Metode Melukis Kaligrafi Allah + Muhammad - Rizki Dwi Cahyono; Joni Haryanto; Erna Dwi Wahyuni; Wimar Anugrah Romadhon (Jurnal Kesehatan Manarang, 2020)
Brain changes that occur in the aging process including structure and function make it easier for the elderly to forget new information that they have just received, known as dementia. The right method to improve the symptoms of dementia is by painting the calligraphy "Allah + Muhammad". The research objective was to determine the effect of the "Allah + Muhammad" calligraphy painting method on improving writing skills and speaking skills in elderly people with dementia. This study used a quasy experimental design. The sample was 22 respondents who were taken based on simple random sampling technique, then made into two groups (intervention: 11 respondents; control: 11 respondents). The independent variable is the method of painting the calligraphy "Allah + Muhammad". The dependent variable is the ability to write and speak. Data collection using MMSE and Tadir questionnaire. Data analysis used the Wilcoxon and Man-Whitney rating test with a significant value of p â‰¤0.05. The results of the Wilcoxon sign rating test in the experimental group for the MMSE test p = 0.007; Tadir test for speaking ability p = 0.008; and for writing ability p = 0.20. While in the control group for the MMSE test p = 0.309; Tadir test for speaking ability p = 0.414; and writing ability p = 1,000. Man-Whitney test results for MMSE p = 0.036; Tadir test for speaking ability p = 0.000; and for writing ability p = 0.002. It can be concluded that the method of painting calligraphy "Allah + Muhammad" can improve writing and speaking skills in elderly people with dementia. The suggestion expected from this research is that elderly nurses can provide the implementation of calligraphy painting in dementia elderly so that the elderly can apply it in their daily life.